Novel iron(iii) catalyst for the efficient and selective coupling of carbon dioxide and epoxides to form cyclic carbonates. Issue 1 (29th October 2014) - Buonerba, Antonio; De Nisi, Assunta; Grassi, Alfonso; Milione, Stefano; Capacchione, Carmine; Vagin, Sergei; Rieger, Bernhard
Abstract : "Re-cycling carbon dioxide with iron". The synthesis of cyclic organic carbonates was accomplished by the coupling of CO2 and epoxides, using a novel air-stable and easy-to-handle iron(iii ) catalyst. Abstract : " Re-cycling carbon dioxide with iron ". The synthesis of cyclic organic carbonates in high yield, stereo- and chemo-selectivity was accomplished through the coupling of carbon dioxide and epoxides, catalysed by a novel air-stable and easy-to-handle thioether-triphenolate iron(iii ) complex.